2013
DOI: 10.1063/1.4848815
|View full text |Cite
|
Sign up to set email alerts
|

Structural investigations of hydrogenated epitaxial graphene grown on 4H-SiC (0001)

Abstract: Structural investigations of hydrogenated epitaxial graphene grown on SiC(0001) are presented. It is shown that hydrogen plays a dual role. In addition to contributing to the well-known removal of the buffer layer, it goes between the graphene planes, resulting in an increase of the interlayer spacing to 3.6 Å–3.8 Å. It is explained by the intercalation of molecular hydrogen between carbon planes, which is followed by H2 dissociation, resulting in negatively charged hydrogen atoms trapped between the graphene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(67 citation statements)
references
References 41 publications
5
61
0
Order By: Relevance
“…We have used this setup to measure the diracted intensity around standard angular positions for (002) reection of graphite and (001) reection of GO assemblies. We have also directed our attention to the angular position of (10) [19,20].…”
Section: X-ray Diractionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have used this setup to measure the diracted intensity around standard angular positions for (002) reection of graphite and (001) reection of GO assemblies. We have also directed our attention to the angular position of (10) [19,20].…”
Section: X-ray Diractionmentioning
confidence: 99%
“…Carbon nanotube (CNT) Buckypaper [19] and GO paper [1012] have been already extensively studied even before the onset of graphene era.…”
Section: Structural and Electronic Properties Of Graphenementioning
confidence: 99%
“…14). Up to this moment we considered only the literature reports devoted to propane-argon assisted growth, but there is also some interesting experimental data on CVD growth of graphene by using hydrogen as a carrier gas [114,126,129,131,132,136]. Michon et al [114,126,129] demonstrated the possibility of direct growth of graphene on 6H-SiC (0001) and 3C-SiC/Si substrates.…”
Section: Growth Of Graphene On Sic Using External Sourcesmentioning
confidence: 99%
“…The most widely studied among the carbon sources is propane [114,121,124,126,[128][129][130][131][132][133][134][135][136][137]. There is only a few works devoted to ethene [125], toluene [127] and xylene [127] as carbon sources for graphene growth on silicon carbide.…”
Section: Growth Of Graphene On Sic Using External Sourcesmentioning
confidence: 99%
See 1 more Smart Citation